Neurosciences in psychiatric expert reports: findings from focus groups - Γκότση (Georgia Martha Gotsi), Γεωργία Μάρθα (Bioethica, 2019)
Neuroscience is a rapidly growing scientific field, whose recent findings gain major interest in the field of criminal law and forensic psychiatry. Neuroscientific evidence is increasingly being used in criminal trials as part of psychiatric testimony, particularly in the US, but also in Europe. This article presents the findings of an empirical study with focus groups involving judges, lawyers, psychiatrists and neurologists, aiming to examine through a focus group interaction process, the use of neuroscientific data in psychiatric testimony from the perspective of all the actors involved in the criminal proceedings. In particular, the study aims to examine the way that neuroscientific evidence would likely be used by lawyers, the way that this evidence is perceived and interpreted by judges, as well as the opinion of psychiatrists - experts and neuroscientists concerning the usefulness, effectiveness and limitations of neurosciences’ use in criminal courts, especially in relation with the assessment of guilt and the assessment of the recidivism risk posed by an offender.